Determination of amount of irrigation and nitrogen for comprehensive growth of greenhouse cucumber based on multi-level fuzzy evaluation - He, Zhihao; Hong, Tingting; Cai, Zelin; Yang, Zhi; Li, Manning; Zhang, Zhi (International Journal of Agricultural and Biological Engineering, 2021)
In the northwestern part of China, rational and efficient management of irrigation and nitrogen significantly affects the intensive production of greenhouse cucumbers (Cucumis sativus L). To evaluate the effects of different combinations of water use and nitrogen (N) on yield, quality, and profitability of the greenhouse cucumbers that planted in 2018 Spring, nine combined treatments were applied. Results indicated the optimal irrigation and nitrogen demands for yield, quality and other indicators were different. The irrigation amount significantly affected the yield, and the yield gradually increased with increasing in irrigation. Single fruit weight (SFW) was significantly affected by the amount of irrigation, nitrogen and their interactions, and the higher amounts of N and irrigation were beneficial to the increase of SFW. The partial factor productivity of the applied N (PFPN) gradually increased with the nitrogen amount decline. Irrigation water use efficiency (IWUE) was closely related to the amount of irrigation. The higher irrigation amount would lead to the lower IWUE. When the amounts of irrigation and nitrogen were at an intermediate level, the content of vitamin C (VC) reached the maximum. As the amount of nitrogen was increased or irrigation was decreased, the Nitrate content (NC) would increase. Free amino acid (FAA) and NC followed a similar variation. When the amounts of irrigation and nitrogen both were at medium levels, the total soluble sugar concentration (TSSC) reached the highest. The multi-level fuzzy evaluation method was used to evaluate different indicators of cucumber. The weights of indicators in the first and second layer were determined by analytic hierarchy process (AHP) and entropy weight method, respectively. Then the fuzzy algorithm was used to comprehensively evaluate all the treatments. The evaluation results show that T4 (irrigation, 1957.6 m3/hm2; N, 210 kg/hm2) is the best strategy for greenhouse cucumber irrigation and nitrogen management in the northwestern part of China. Keywords: Cucumis sativus L, water and nitrogen coupling, yield, PFPN, IWUE, quality, multi-level fuzzy evaluation DOI: 10.25165/j.ijabe.20211402.5785 Citation: He Z H, Hong T T, Cai Z L, Yang Z, Li M N, Zhang Z. Determination of amount of irrigation and nitrogen for comprehensive growth of greenhouse cucumber based on multi-level fuzzy evaluation. Int J Agric & Biol Eng, 2021; 14(2): 35–42.